Analisis Penerapan Sistem Akuntansi Manajemen terhadap Pengendalian Kualitas Produk di Rumah Jahit Akhwat Makassar - Nurul Afiqah Annas; Andi Aris Mattunruang; Nurul Wahyuni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the application of management accounting systems to product quality control at Rumah Jahit Makassar. The research method used is a qualitative approach with the research respondents being the head of Rumah Jahit Akhwat Production, Perintis branch. The results of the study indicate that in product quality control three SAM components are used, namely quality targets, quality feedback, and quality incentives. The company controls the products produced to minimize the production of defective or damaged products. All information can be presented using SAM to determine the condition of product quality and the performance of production employees in producing goods. Companies that implement SAM will be able to manage both data into information so that they can present reports. This report is used to assist managers in making decisions.